2007
DOI: 10.1073/pnas.0701331104
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin/CBP signaling maintains long-term murine embryonic stem cell pluripotency

Abstract: Embryonic stem cells (ESCs) represent an important research tool and a potential resource for regenerative medicine. Generally, ESCs are cocultured with a supportive feeder cell layer of murine embryonic fibroblasts, which maintain the ESCs' capacity for selfrenewal and block spontaneous differentiation. These cumbersome conditions, as well as the risk of xenobiotic contamination of human ESCs grown on murine embryonic fibroblasts, make it a priority to develop chemically defined methods that can be safely use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
279
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(297 citation statements)
references
References 37 publications
15
279
1
2
Order By: Relevance
“…This differential role might be associated to the regulation of AKT by different complexes (Guertin et al, 2006). Similar results have been described for β-catenin in mESC, where it has opposite effects depending on the complex it binds to (Miyabayashi et al, 2007). In this regard, we have not observed any contribution to pluripotency maintenance by CnAβ1, whereas we found a significant downregulation of ESC differentiation towards the mesoderm lineage after CnAβ1 depletion.…”
Section: Discussionsupporting
confidence: 88%
“…This differential role might be associated to the regulation of AKT by different complexes (Guertin et al, 2006). Similar results have been described for β-catenin in mESC, where it has opposite effects depending on the complex it binds to (Miyabayashi et al, 2007). In this regard, we have not observed any contribution to pluripotency maintenance by CnAβ1, whereas we found a significant downregulation of ESC differentiation towards the mesoderm lineage after CnAβ1 depletion.…”
Section: Discussionsupporting
confidence: 88%
“…; 76.3 AE 1.33%) was significantly lower than those of ESCs cultured in a 2D microenvironment with (84.5 AE 6.95%) or without (84.4 AE 6.95%) a MEF feeder layer. Thus, these studies showed that a synthetic 3D For identifying signal proteins regulated by downstream signaling derived from combinatorial activation of each integrin heterodimer, we investigated transcription and translation of Stat3 [34,35], b-catenin [36,37], Smad 1/5/8 [38] and Akt1 [39,40] genes and proteins, which have been reported as key signal molecules supporting stem cell self-renewal. In the case of Stat3 activated by LIF ( Supplementary Fig.…”
Section: Development Of Synthetic 3d Integrin-stimulating Matrices Sumentioning
confidence: 99%
“…The mechanism of action was found to be independent of known self-renewal pathways thought to be essential (BMP4/Smad-Id [19], Wnt/B-catenin [20], LIF/STAT3 [21]). Instead, pluripotin was characterized as a dual inhibitor of extracellular signalregulated kinase-1 (ERK1) and RasGAP, two differentiation-inducing proteins.…”
Section: Role Of Small Molecules In Stem Cell Fieldmentioning
confidence: 98%
“…This hypothesis is supported by a study by Ying et al [25], in which a combination of glycogen synthase kinase-3 (GSK-3) inhibitor, CHIR99021 and mitogen-activated protein kinase (MEK) inhibitor, PD0325901, could maintain long-term self-renewal of mESCs in the absence of exogenous cytokines [25]. Other small molecules which has been used to maintain mouse ES cells in pluripotent state include PD98059, a MEK inhibitor, 6-Bromoindirubin-3'-oxime (BIO), another GSK-3 inhibitor/Wnt signaling activator, and IQ-1, a modulator of Wnt/CBP signalling (Table 1) [20]. In addition to synthetic small molecules, certain physiological small molecules are capable of enhancing ES self-renewal.…”
Section: Role Of Small Molecules In Stem Cell Fieldmentioning
confidence: 99%